Bioprocessing of Spent Coffee Grounds as a Sustainable Alternative for the Production of Bioactive Compounds - Karla A. Luna; Cristóbal N. Aguilar; Nathiely Ramírez-Guzmán; Héctor A. Ruiz; José Luis Martínez; Mónica L. Chávez-González (Fermentation)
Spent coffee grounds are the most abundant waste generated during the preparation of coffee beverages, amounting to 60 million tons per year worldwide. Excessive food waste production has become a global issue, emphasizing the need for waste valorization through the bioprocess of solid-state fermentation (SSF) for high added-value compounds. This work aims to identify the operational conditions for optimizing the solid-state fermentation process of spent coffee grounds to recover bioactive compounds (as polyphenols). An SSF process was performed using two filamentous fungi (Trichoderma harzianum and Rhizopus oryzae). An exploratory design based on the Hunter & Hunter method was applied to analyze the effects of key parameters such as inoculum size (spores/mL), humidity (%), and temperature (°C). Subsequently, a Box–Behnken experimental design was carried out to recovery of total polyphenols. DPPH, ABTS, and FRAP assays evaluated antioxidant activity. The maximum concentration of polyphenols was observed in treatment T3 (0.279 ± 0.002 TPC mg/g SCG) using T. harzianum, and a similar result was obtained with R. oryzae in the same treatment (0.250 ± 0.011 TPC mg/g SCG). In the Box–Behnken design, the most efficient treatment for T. harzianum was T12 (0.511 ± 0.017 TPC mg/g SCG), and for R. oryzae, T9 (0.636 ± 0.003 TPC mg/g SCG). These extracts could have applications in the food industry to improve preservation and functionality.